Analisis Produktivitas pada Mesin BM 206 D-2 Menggunakan Metode Total Productive Maintenanace (TPM) dengan Pendekatan Overall Equipment Efectiveness (OEE) di PT. Berlina Tbk - Rega Gilang Renaldy; Subchan Asy’ari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Productivity is key to success in the manufacturing industry, particularly at PT.BERLINA Tbk, which specializes in plastic packaging manufacturing. This study focuses on enhancing the operational effectiveness of the BM 206 D-2 machine trough the implementation of Total Productive Maintenance (TPM) and measurement of Overall Equipment Effectiveness (OEE) as well as the identification and mitigation of Six Big Losses. The research involves two sampling periods, each spanning two quarters. During the first period, the average OEE value of 66% indicated that the greatest losses were due to machine breakdown or Breakwon Losses, related to deficiencies in operator and technician skills, inadequate planes maintenance, and machine cleanliness. Following the implementation of improvements based on these findings, the average OEE incrased to 71% in the second period. These results underscore the importance of enhancing technical skills, effective maintenance, and strict cleanliness to improve productivity and reduce production losses.